1995
DOI: 10.1016/0014-5793(95)00234-z
|View full text |Cite
|
Sign up to set email alerts
|

Deficiency of ganglioside biosynthesis in metastatic human melanoma cells: relevance of CMP‐NeuAc: LacCer α2‐3 sialyltransferase (GM3 synthase)

Abstract: The glycosphingolipid patterns were analyzed on two clones derived from a human melanoma cell line and selected for their respectively high and low metastatic ability in immunosuppressed newborn rats. Conversely to the weakly metastatic cells which exhibited a pattern similar to that of the parental cell line, highly metastatic human melanoma cells appeared to be deficient in ganglioside biosynthesis. An accumulation of lactosylceramide was found in the latter cells, with low amounts of GM3 as the only ganglio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
17
1

Year Published

1996
1996
2004
2004

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(18 citation statements)
references
References 29 publications
0
17
1
Order By: Relevance
“…In addition, while changes in cell surface sialic acids have been shown to affect attachment of murine lymphoma cells to type IV collagen and fibronectin (Dennis et al, 1982), sialidase transfection did not alter the attachment to the extracellular matrix in our experiments. Zebda et al (1995) have reported that GM3 biosynthesis is decreased in highly metastatic human melanoma cells, which appears to contradict our conclusion that GM3 reduction occurs in cells with suppressed metastatic ability. The GM3 reduction in our study appeared to occur mainly in the cytosol compartment but hardly on the cell surface, though the possibility that surface GM3 also might be decreased cannot be excluded because of accessibility of anti-GM3.…”
Section: Discussioncontrasting
confidence: 55%
“…In addition, while changes in cell surface sialic acids have been shown to affect attachment of murine lymphoma cells to type IV collagen and fibronectin (Dennis et al, 1982), sialidase transfection did not alter the attachment to the extracellular matrix in our experiments. Zebda et al (1995) have reported that GM3 biosynthesis is decreased in highly metastatic human melanoma cells, which appears to contradict our conclusion that GM3 reduction occurs in cells with suppressed metastatic ability. The GM3 reduction in our study appeared to occur mainly in the cytosol compartment but hardly on the cell surface, though the possibility that surface GM3 also might be decreased cannot be excluded because of accessibility of anti-GM3.…”
Section: Discussioncontrasting
confidence: 55%
“…As predicted, plasma GSL analysis of individuals with mutant GM3 synthase shows a lack of flux through the GM3-catalyzed pathway, resulting in an increase in the levels of lactosylceramide and members of the alternative biosynthetic pathways. A related phenomenon was observed in a highly metastatic human melanoma cell line 15 , in which reduced GM3 synthase activity resulted in decreased levels of GM3, low levels of other gangliosides and a concomitant increase in lactosylceramide. We have no data on brain GSLs from affected members of these families, but o-series gangliosides may be the dominant GSL species synthesized, with the possibility of elevated lactosylceramide, depending on the relative flux through the o-series pathway in humans in the absence of GM3 synthase.…”
Section: E T T E R Smentioning
confidence: 77%
“…In the situation where GD2 and GM3 are critical factors in blocking LC differentiation, it is unlikely that both melanoma clones would alter LC generation, because of their distinct ganglioside profiles; IC8 melanoma cells mainly express GM3, GM2, GD3 and GD2, whereas TIC3 cells only express low levels of GM3 (Zebda et al, 1994b). Thus, none of the characterized tumour-derived factors able to block the DC differentiation were found to be effective in our co-culture system.…”
Section: Discussionmentioning
confidence: 90%